2022
DOI: 10.11124/jbies-22-00254
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes self-management education for older adults in Western countries: a scoping review protocol

Abstract: Objective: This scoping review will map the available evidence on diabetes self-management education programs for older adults in Western countries. Introduction: Self-management and education are crucial for controlling diabetes and its associated complications. The successful uptake of diabetes self-management education programs is not straightforward, and little is known about diabetes programs for older adults. Within this context, a broad overview of diabetes self-management education for older adults, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…This scoping review was conducted following the JBI methodology framework for scoping reviews [ 47 ], and we adhered to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses Extension for Scoping Reviews (PRISMA-ScR) checklist [ 47 ] ( S1 Appendix ). Our published protocol [ 46 ] was registered through Open Science Framework and is available at https://doi.org/10.17605/OSF.IO/W4KCQ . Our overall review question was: What has been reported in the literature about DSME for older persons aged 65 years and older living with T1D and T2D?…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…This scoping review was conducted following the JBI methodology framework for scoping reviews [ 47 ], and we adhered to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses Extension for Scoping Reviews (PRISMA-ScR) checklist [ 47 ] ( S1 Appendix ). Our published protocol [ 46 ] was registered through Open Science Framework and is available at https://doi.org/10.17605/OSF.IO/W4KCQ . Our overall review question was: What has been reported in the literature about DSME for older persons aged 65 years and older living with T1D and T2D?…”
Section: Methodsmentioning
confidence: 99%
“…People aged 65 years and over have been frequently excluded from research (e.g., clinical trials); when included, researchers often do not report analysis by age [ 48 , 49 ]. Our review was not specific to gender, sex, ethnicity, or frailty [ 46 ]. Studies including older persons with and without diabetes were considered when separate analyses for people with and without diabetes were provided [ 46 ].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations